Viabilidade técnica e econômica da permeável e irrigação em lavouras de cafeeiro arábica em formação - ALVES NETO, Dorival (2018)
The training stage of coffee is among the most costly practices for the producer, having the weed control, as well as the maintenance and / or replacement of water for plants, a significant role in plant development and production costs. Thus, the objective of this research was to evaluate the technical and economic viability of the permeable mesh in the formation of arabica coffee crops with irrigation. The experiment was installed and developed in the coffee sector of IFSULDEMINAS – Campus Muzambinho. The experimental design was randomized blocks (RBD) with 6 replicates. The treatments were: with mesh and with irrigation (WMWI); with mesh and without irrigation (WMWOUT); without mesh and with irrigation (WOUTMWI); and without mesh and without irrigation (WOUTMWOUTI). The plants used were of the cultivar Catuai Amarelo IAC 62 and the spacing adopted was 0.70 x 3.50 meters, totaling 720 plants. It was concluded that the WMWI coffee and WMWOUTI coffee presented the best coffee development results in all variables analyzed, compared to WOUTMWOUTI. In the coffee production, the reduction of manpower costs in the second year reached 60.61% for WMWI coffee and 65.61% for WMWOUTI coffee, WOUTMWI coffee was 13.64% higher for the same year. Each technology has generated in 2 years total expenses (manpower and investments), in the order of R$ 24,890,08/ha (WMWI), R$ 9,445,66/ha (WMWOUTI), R$ 19,336,86/ha (WOUTMWI), all above the WOUTMWOUTI, which had a cost with manpower the value of R$ 3,778,83/ha. It can be noticed that both the mesh and the irrigation showed favorable results, the first one by the reduction of the manpower, the second by the replenishment of water to the plants and both contributing to the development of the coffee, may become viable mechanisms for producers of our region, from the productive gains offered by the better development of coffee.